2005
DOI: 10.1093/ije/dyi078
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and its relation to risk factors for cardiovascular disease in the north-west of Russia: the Arkhangelsk study

Abstract: Background To explore indicators and levels of alcohol consumption in a Russian population, and to elaborate these in relation to risk factors for cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 31 publications
3
46
2
1
Order By: Relevance
“…A very recent study from the northwest region of Russia revealed GGT levels in both sexes that were more than twice as high as those found in comparable studies. 34 This study offers further evidence that elevated GGT is significantly associated with increased risk for CVD.…”
Section: Discussionsupporting
confidence: 54%
“…A very recent study from the northwest region of Russia revealed GGT levels in both sexes that were more than twice as high as those found in comparable studies. 34 This study offers further evidence that elevated GGT is significantly associated with increased risk for CVD.…”
Section: Discussionsupporting
confidence: 54%
“…The harmful drinking might be responsible for these gender differences. The population surveys from Russia show consistently higher rates of binge drinking among men than women [17,18].…”
Section: Discussionmentioning
confidence: 97%
“…The population surveys from Russia show consistently higher rates of binge drinking among men than women. Indeed, the results of study carried out in Archangelsk suggest that 61.9% of male and 25.7% of female industrial workers had a consumption pattern that was hazardous according to the AUDIT definition (Nilssen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%